Strategic management : text, tools, and cases for business policy - Comerford, Robert A.; Callaghan, Dennis W. (Boston, Mass. : Kent Pub. Co., 1985)
The book explains the processes of strategic management so that students will be able to implement it in case analyses and in real organizations.
Includes bibliographical references and index.
occ 16/01/2019
Loans
Keywords: Business planning